Dendrokronološke raziskave na Založnici - najmlajši znani bakrenodobni koliščarski naselbini na Ljubljanskem barju - Čufar, Katarina (Zbornik gozdarstva in lesarstva, 2003)
Investigations in wood and archaeological artefacts collected during rescue excavations in the drainage ditches on the location of copper-age, i. e. Eneolithic pile dwelling Založnica at Ljubljansko barje (Ljubljana Moors, Slovenia) are presented. 35% of 1315 samples were dendrochronologically investigated. We constructed three tree-ring chronologies, two of ash-wood (Fraxinus sp.) and one of oak (Quercus sp.), and reconstructed the building activities that occurred in the period of 90 years. We found out that the activities in Založnica coincided with those in another pile dwelling Parte, which existed in the same period and was located 10 km away from Založnica. Based on radiocarbon dating, the activities in Založnica ended in the 25th century BC. The last 40 years of the settlement delineate the youngest Copper Age settlement at Ljubljansko barje and in Slovenia. We describe how the dated wood and its relation to other archaeological artefacts helped us to place Zloznica in the Somogyvár-Vinkovci culture. This cultural classification constitutes a new interpretation of settlement activities before the Bronze Age began at Ljubljansko barje, in Slovenia in general, and in the neighbouring countries.
Keywords: archaeology; arheologija; dendrokronologija; les; Ljubljana Marshes; Ljubljansko barje